Advanced Legal Research Process and Practice - Austin, Megan (Open textbook library., 2023)
Written for students and instructors in an advanced legal research course, this book uses the steps of the legal research process to facilitate skills practice, collaboration, and reflection. It proposes a hypothetical as a basis for practicing the research process steps and encourages students and instructors to contribute other hypotheticals. The text also includes sample assignments, demonstration videos, and discussion and reflection questions, with opportunities for students and instructors to contribute additional questions. This text uses an approach that emphasizes student reflection on the development of research skills, with the benefit of repeated and consistent formative feedback.